Purchasing and supply chain management a sustainability perspective - Johnsen, Thomas E.; Howard, Mickey 1967-; Miemczyk, Joe (Routledge, 2014)
"Supply chain management is a cross-functional business concept that includes, for example, logistics and operations management. In many organizations purchasing is now part of the supply chain management function. In addition, the age of the "triple bottom line" is upon us: the issue of sustainability seems certain to gain great momentum and a company is no more sustainable than the suppliers it sources from which